A INOVAÇÃO NO SISTEMA CARCERÁRIO BRASILEIRO COM O USO DO MONITORAMENTO ELETRÔNICO - Campos, Cliver Lucas Silveira (2019)
Currently one of the major problems faced by Brazilian society concerns the incarceration, its financial and social cost and, finally, the process of resocialization of the offending individual. Given the data collected on the Brazilian criminal system, it is possible to notice a high budget value per individual incarcerated. In addition to budgetary problems, prison overcrowding directly affects basic human rights, even if they refer to violating individuals. Given the problems mentioned, this work aims to investigate the economic, social and technological viability of the innovation of the electronic monitoring system in the state of Paraná. Specifically, we seek to survey the history of Brazilian criminal laws; to study the evolution of the electronic monitoring system and its viability as a tool for inspection of the convicted in the state of Paraná, besides analyzing the Social Office, as a social innovation tool coupled with the technological innovation of the anklets in the state of Paraná, notably the city of Guarapuava / PR. This work therefore brings the impact of applying both technological and social innovation techniques, making unprecedented and innovative use of available partner technologies and policies. Thus, we conclude that the replacement of traditional incarceration by the use of electronic monitoring, combined with the attendance of the Social Office, may provide the appropriate social assistance, and may even considerably reduce the cost of the penal system, as well as make it more affordable. efficient, reducing criminal recidivism by offending individuals.